Idiopathic ulcerative laryngitis causing midmembranous vocal fold granuloma1. (18th September 2012) - Sinclair, Catherine F.; Sulica, Lucian
Abstract Idiopathic ulcerative laryngitis (IUL) is characterized by bilateral midmembranous vocal fold ulceration, which follows upper respiratory infection with cough. In contrast, granuloma of the membranous vocal fold can occur rarely following microlaryngoscopy, presumably secondary to surgical violation of deep tissue planes. We report a novel case of noniatrogenic membranous vocal fold granulation developing in a patient with IUL. Although the presence of granulation implied injury to the entire microstructure of the vibratory portion of the vocal fold, the lesion resolved with conservative management without adverse sequelae.